2019
DOI: 10.1186/s13054-019-2604-5
|View full text |Cite
|
Sign up to set email alerts
|

Rescue fecal microbiota transplantation for antibiotic-associated diarrhea in critically ill patients

Abstract: BackgroundAntibiotic-associated diarrhea (AAD) is a risk factor for exacerbating the outcome of critically ill patients. Dysbiosis induced by the exposure to antibiotics reveals the potential therapeutic role of fecal microbiota transplantation (FMT) in these patients. Herein, we aimed to evaluate the safety and potential benefit of rescue FMT for AAD in critically ill patients.MethodsA series of critically ill patients with AAD received rescue FMT from Chinese fmtBank, from September 2015 to February 2019. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 43 publications
0
50
0
1
Order By: Relevance
“…The experience of the use of FMT in critically ill patients is very limited [106,[108][109][110]. A recent multi-center study in critically ill patients with antibiotic-associated diarrhea reported beneficial effects after FMT, including the reduction of abdominal pain, diarrhea, abdominal distension, and hematochezia [111]. Within the first days of the FMT, a reduction in fever and amelioration of the systemic inflammatory response syndrome (SIRS) was observed in all patients.…”
Section: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%
“…The experience of the use of FMT in critically ill patients is very limited [106,[108][109][110]. A recent multi-center study in critically ill patients with antibiotic-associated diarrhea reported beneficial effects after FMT, including the reduction of abdominal pain, diarrhea, abdominal distension, and hematochezia [111]. Within the first days of the FMT, a reduction in fever and amelioration of the systemic inflammatory response syndrome (SIRS) was observed in all patients.…”
Section: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%
“…Additionally, fecal transplantation was approved for clinical trials as a therapeutic option for SARS-CoV-2-related pneumonia based on the promising results obtained from fecal microbiota transplantation in patients suffering from antibiotic-associated diarrhea, active ulcerative colitis, and other viral infections [103][104][105][106]. Recently, it was found that intestinal microbiota-derived IFN in lung stroma confers protection against viral diseases such as avian influenza and respiratory syncytial virus [103].…”
Section: Control and Treatment Of Covid-19 Infectionmentioning
confidence: 99%
“…44.4% of patients recovered from abdominal symptoms without return and survived for at least 12 weeks after being discharged from the ward. 100% of abdominal pain, 86.7% of diarrhea, 69.2% of abdominal distention, and 50% of hematochezia were improved after FMT [42]. Eight deaths, which were unrelated to transplantation, occurred during this time.…”
Section: The Use Of Fmt In Other Intestinal Disordersmentioning
confidence: 79%